Interrelations of muscle functional MRI, diffusion-weighted MRI and 31P-MRS in exercised lower back muscles - Hiepe, Patrick; Gussew, Alexander; Rzanny, Reinhard; Anders, Christoph; Walther, Mario; Scholle, Hans-Christoph; Reichenbach, Jürgen R. (NMR in biomedicine, 2014)
Exercise‐induced changes of transverse proton relaxation time (T2), tissue perfusion and metabolic turnover were investigated in the lower back muscles of volunteers by applying muscle functional MRI (mfMRI) and diffusion‐weighted imaging (DWI) before and after as well as dynamic 31P‐MRS during the exercise. Inner (M. multifidus, MF) and outer lower back muscles (M. erector spinae, ES) were examined in 14 healthy young men performing a sustained isometric trunk‐extension. Significant phosphocreatine (PCr) depletions ranging from 30% (ES) to 34% (MF) and Pi accumulations between 95% (left ES) and 120%–140% (MF muscles and right ES) were observed during the exercise, which were accompanied by significantly decreased pH values in all muscles (∆pH ≈ –0.05). Baseline T2 values were similar across all investigated muscles (approximately 27 ms at 3 T), but revealed right–left asymmetric increases (T2,inc) after the exercise (right ES/MF: T2,inc = 11.8/9.7%; left ES/MF: T2,inc = 4.6/8.9%). Analyzed muscles also showed load‐induced increases in molecular diffusion D (p = .007) and perfusion fraction f (p = .002). The latter parameter was significantly higher in the MF than in the ES muscles both at rest and post exercise. Changes in PCr (p = .03), diffusion (p < .01) and perfusion (p = .03) were strongly associated with T2,inc, and linear mixed model analysis revealed that changes in PCr and perfusion both affect T2,inc (p < .001). These findings support previous assumptions that T2 changes are not only an intra‐cellular phenomenon resulting from metabolic stress but are also affected by increased perfusion in loaded muscles. Copyright © 2014 John Wiley & Sons, Ltd. This work analyzed the effects of energy metabolite turnover and vascular perfusion on load‐induced T2 changes in skeletal muscles of young and healthy subjects by combining muscle functional (T2‐weighted) MRI (mfMRI), 31P‐ chemical shift imaging (CSI) and diffusion‐weighted MRI. In particular, it was demonstrated that mfMRI‐related T2 increases strongly vary inter‐individually and are associated with changes in muscle perfusion and intra‐cellular metabolic turnovers as well as with the rate of perceived exertion.